“Diseño del sistema de control interno para cuentas por cobrar de la empresa Industria Licorera Embotelladora de Loja S.A., periodo 2023” - Alverca Jiménez, Lisseth del Cisne (2024)
The curricular integration project entitled "Design of an Internal Control System for Accounts Receivable at Industria Licorera Embotelladora de Loja S.A., 2023" was conducted to develop detailed procedures and clear policies for the management of accounts receivable, encompassing invoicing, payment tracking, and collection management. Additionally, the project aimed to delineate the roles and responsibilities of employees involved in the accounts receivable process, thereby enabling users to comprehend operations and processes for more optimal and efficient control within the company. The completion of this project required the utilization of bibliographic materials, as well as a field study to gather the necessary data for an institutional diagnosis. An interview and a survey were conducted with key personnel in the accounts receivable department, including the general manager, financial manager, accountant, collection assistant, sales supervisor, and sales representatives, to identify internal deficiencies. As a result, a manual was developed that includes specific policies, procedures, and flowcharts for the accounts receivable department. This manual outlines the steps to be followed from invoicing and credit receipt to the recovery and recording of outstanding receivables, establishing policies that ensure efficient compliance. The information generated will enable management to make informed and effective decisions, thereby facilitating the achievement of the company's objectives. Finally, conclusions and recommendations were formulated for potential implementation at Industria Licorera Embotelladora de Loja S.A.